Comparison of the anatomical and functional success of fascia and perichondrium grafts in transcanal endoscopic type 1 tympanoplasty - Kadir Özdamar; Alper Sen (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background There are no studies in the literature, comparing the functional and anatomical successes of the use of fascial and perichondrial grafts in endoscopic type 1 tympanoplasties. Objectives To compare the anatomical and functional outcomes of grafting with the fascia of the temporalis muscle and with the perichondrium of the tragal cartilage in patients undergoing primary transcanal type 1 tympanoplasty with endoscopy. Methods We enrolled a total of 151 patients (80 females and 71 males with a mean age of 26.0 ± 9.3 years in the age range between 18-57) with MERI scores ranging from 1 to 3 and who underwent a transcanal endoscopic type 1 tympanoplasty without tympanomeatal flap elevation. The patients were assigned to two groups according to the type of the graft used. The patients were assigned to either the tragal cartilage perichondrium group (Group A) or the fascia of the temporal muscle (Group B). The groups were compared according to the pre- and postoperative air-bone gaps and to the status of the tympanic membrane. Results There were no statistically significant differences in the distribution of the age, gender, localization, MERI scores, the duration of the operation, and the size of the perforation (all p values> 0.05). The pre-operative air-bone gap values of Group A and B did not show a statistically significant difference (p = 0.073). The postoperative improvement in the air-bone gap value did not demonstrate a significant difference between Group A and B (p = 0.202). The graft retention rates were 94.9 and 97.2% in Group A and in Group B respectively. There were no statistically significant differences between the two groups in terms of the graft retention success rates (p = 0.743). Conclusion Perichondrium and fascia were suitable for use in endoscopic tympanoplasties.